Granulocytic sarcoma preceding AML M0 and the diagnostic value of CD34. Issue 9 (1st September 1999) - Astall, E; Yarranton, H; Arno, J; Marcus, R
Abstract : Granulocytic sarcoma with no demonstrable abnormalities in the peripheral blood or bone marrow is a rare but recognised initial manifestation of acute myeloid leukaemia and has led to diagnostic difficulties in some cases. A lymph node excisional biopsy from a patient presenting with cervical lymphadenopathy, a mediastinal mass, and a normal peripheral blood picture was reported to have features suggesting a T cell non-Hodgkin lymphoma, for which she was subsequently treated. However, 10 months later the patient developed acute myeloid leukaemia, FAB classification M0. The initial lymph node biopsy was reviewed and further immunohistochemical studies using antibodies against CD34 led to a revised diagnosis of primary granulocytic sarcoma.